Resisting the “Empirical” Empire: Reclaiming Palestinian Knowing in a Time of Scholasticide: Reclaiming Palestinian Knowing in a Time of Scholasticide - Atallah, Devin George (PINS-Psychology in Society, 2025)
Scholasticide is a term that connotes the systematic racist attack against Palestinian knowledge and education. During the ongoing genocide, this scholasticide has intensified to an unimaginable degree, evidenced, for example, by Israel murdering thousands of Palestinian professors and students, destroying all universities and schools across Gaza. In this paper, I seek to reveal and analyze critical elements of scholasticide as I, myself, was being pushed out of a US-based university due to anti-Palestinian racism. I share my response to a statement written against me by two anonymous psychology department colleagues in my university who succeeded in advocating for the initial denial of my tenure. Central to their argument was that my scholarship on Palestinian trauma, grief, and decolonial healing was not “empirical” enough. In my response, I challenge this commonplace academic practice of defending “empiricism” while masking underlying racism that delegitimizes decolonial knowledges worldwide.